Hot melt adhesive and use thereof
A hot melt adhesive blend of polypropylene-ethylene copolymers with a tackifier achieves flexibility and cohesion, addressing the balance issue in existing adhesives, providing strong bonding at low temperatures and preventing oil migration.
Patent Information
- Application Number
- CN202410053599.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-15
- Publication Date
- 2025-07-15
AI Technical Summary
The existing olefin-based hot melt adhesives are difficult to achieve a balance between flexibility and cohesion, and there are problems with oil leakage and migration, so they cannot be effectively bonded to the substrate.
A hot melt adhesive is prepared using a specific proportion of the first and second polypropylene-polyethylene copolymer mixture, combined with a tackifier, wax or polyolefin liquid plasticizer and additives, providing flexibility and adhesion and spraying at low application temperatures.
High initial strength and excellent bond strength to the substrate at low application temperatures are achieved, avoiding oil leakage and thermally sensitive substrate burning through, providing a balance of flexibility and adhesion.
Smart Images

Figure BDA0004663837160000091 
Figure BDA0004663837160000101 
Figure BDA0004663837160000111
Abstract
Description
Field of the Invention
[0001] The present invention relates to a hot melt adhesive composition prepared from a mixture of propylene copolymers. The hot melt adhesive composition contains very little or even no oil, while providing high cohesion and excellent adhesion to nonwoven substrates and polymer films. The hot melt adhesive composition is particularly suitable for manufacturing absorbent structural articles. Background Art
[0002] It is difficult to find the right balance between the flexibility and cohesion of olefin-based hot melt adhesives. To achieve this balance, various polymer blends have been used to prepare hot melt adhesives, including blends of hydrogenated styrenic block copolymers and α-olefin copolymers in US2019 / 0382631A1, blends of thermoplastic styrene block copolymers and propylene homopolymers in US 9822283B2; and blends of propylene / butene or propylene / hexene copolymers with polybutene-1 in US2020 / 0157385A1.
[0003] The latest developments in olefin catalysts have provided more economical olefins on the market, especially propylene copolymers. Although propylene polymers have been candidates for hot melt adhesives, their rigidity and inability to adhere to substrates have made them undesirable for use in hot melt adhesives. Rubber-based or amorphous ethylene copolymers are added to reduce the stiffness of propylene polymers; however, finding the right balance between flexibility and cohesion for propylene-based hot melt adhesives has been challenging.
[0004] The hot melt adhesives described in US2017 / 0204306A1 and US2019 / 0144719A1 are prepared from semi-crystalline low molecular weight propylene with a DSC melting enthalpy greater than 35 J / g. Although these adhesives are designed to improve the creep retention of elastic films and elastic threads, they provide insufficient flexibility, as well as wetting and permeability to film substrates at low coating weights.
[0005] The hot melt adhesives described in US2016 / 0102230A1 are prepared from propylene impact copolymers having greater than 90 wt% propylene and a DSC melting point in the range of about 130 °C to about 165 °C. However, softening points greater than 130 °C have high viscosities, and they require higher application temperatures and provide limited processability.
[0006] As described in US2017 / 0290945 A1, for hot melt adhesives prepared from propylene-based copolymers with a melt index of less than about 20 (measured at 190 °C, 2.16 kg), high oil contents, i.e., greater than 20 wt%, are required for adhesives with high viscosities and high application temperatures.
[0007] There is a need in the art for propylene-based hot melt adhesives that have an appropriate balance of flexibility and cohesion, as well as stable adhesive properties, while having minimal or no oil bleeding and migration. The present invention meets this need. SUMMARY OF THE INVENTION
[0008] The present invention provides a hot melt adhesive composition prepared from a mixture of propylene copolymers, which composition is suitable for manufacturing absorbent structural articles.
[0009] One aspect of the present invention is a hot melt adhesive comprising:
[0010] (a) about 20 - about 45 wt% of a polymer mixture composed of (1) and (2):
[0011] (1) A first polypropylene - polyethylene (co)polymer having (i) a viscosity of 3000 cps to 8500 cps at 190 °C, (ii) a DSC melt heat of fusion value of less than about 5 J / g measured at a heating rate of 10 °C / min according to ASTM D3418, and (iii) a DSC melting peak at about 90 - 145 °C measured at a heating rate of 10 °C / min according to ASTM 3418; and
[0012] (2) A second polypropylene - polyethylene (co)polymer having (i) a melt index of about 15 - about 40 g / 10 min at 2.16 kg, 190 °C according to ASTM D1238, and (ii) a DSC melt heat of fusion value of less than about 15 J / g measured at a heating rate of 10 °C / min according to ASTM D3418;
[0013] wherein the mass ratio of the first polypropylene - polyethylene (co)polymer to the second polypropylene - polyethylene (co)polymer is about 3:1 to about 6.5:1;
[0014] (b) about 30 wt% to about 60 wt% of a tackifier
[0015] The hot melt adhesive has (i) a tan(δ) value greater than about 30 at 140 °C, 10 rad / s and (ii) a melt viscosity of about 1,500 cps to about 11,000 cps at 150 °C measured according to ASTM 3236. The hot melt adhesive optionally has up to about 30 wt% of a wax or polyolefin liquid plasticizer;
[0016] In another aspect, the present invention relates to a hot melt adhesive consisting essentially of:
[0017] (a) about 20 - about 45 wt% of a polymer matrix prepared from a mixture of (1) and (2):
[0018] (1) A first polymer system, wherein the first polymer system has (i) a viscosity of 3000 - 8500 cps at 190 °C, (ii) a DSC heat of fusion value of less than about 5 J / g measured at a heating rate of 10 °C / min according to ASTM D3418, (iii) a DSC melting peak at about 90 - 145 °C measured at a heating rate of 10 °C / min according to ASTM 3418, and (iv) propylene and ethylene (co - polymerized) monomers; and
[0019] (2) A second polymer system, wherein the second polymer system has (i) a melt index of about 15 - about 40 g / 10 min at 2.16 kg and 190 °C according to ASTM D 1238, (ii) a DSC heat of fusion value of less than about 15 J / g measured at a heating rate of 10 °C / min according to ASTM D3418, and (iii) propylene and ethylene (co - polymerized) monomers;
[0020] wherein the mass ratio of the first polymer system to the second polymer system is about 3:1 to about 6.5:1;
[0021] (b) About 30 - about 60 wt% of a tackifier.
[0022] (c) About 10 - about 30 wt% of a wax or polyolefin liquid plasticizer; and
[0023] (d) About 0.1 - about 6 wt% of an additive selected from the group consisting of fillers, antioxidants, colorants, fillers, pigments, UV absorbers, UV inhibitors, and compatible coatings for packaging purposes.
[0024] The hot - melt adhesive has (i) a tan(δ) value greater than about 30 at 140 °C and 10 rad / s and (ii) a melt viscosity of about 1,500 cps to about 11,000 cps at 150 °C measured according to ASTM3236. DETAILED DESCRIPTION OF THE INVENTION
[0026] "Absorbent article" refers to a device that absorbs and contains body exudates, and more particularly, to a device that is placed against or adjacent to the body of a wearer to absorb and contain various exudates discharged from the body. Exemplary absorbent articles include diapers, training pants, pull - on diaper pants (i.e., diapers having pre - formed waist and leg openings as shown in U.S. Patent No. 6,120,487), re - fastenable diapers or diaper pants, incontinence briefs and underwear, diaper fasteners and liners, feminine hygiene underwear such as panty liners, absorbent inserts, meat pads, animal pads, face masks, coveralls, etc.
[0027] "Absorbent structure adhesives" refers to adhesives that bond together the components of an absorbent article, including absorbent pads, nonwoven fabrics, topsheets, backsheets, core packs, core stabilizers, and core fasteners.
[0028] "Adhered adhesively" to a substrate, where the adhesive is used to bond to a substrate (e.g., film, polymer film, elastic film, nonwoven fabric, and tissue paper) or to bond to a second, similar or different substrate.
[0029] As used herein, "comprise," "comprising," "comprises," "include," "having," "may," "contain," and variations thereof are open-ended terms, each specifying the presence of the subsequent recited subject matter (e.g., a component), but not precluding the presence of other features (e.g., elements, steps, components known in the art or disclosed herein). However, such descriptions should also be construed as describing the composition or method as "consisting of the recited ingredients / steps," which permits only the presence of the given ingredients / steps and any impurities that may result therefrom, and excludes other ingredients / steps.
[0030] "Consisting essentially of" is used herein to limit the scope of a subject (e.g., the scope of a subject in a claim) to the specified materials or steps and those materials or steps that do not materially affect the basic and novel characteristics of the subject.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. In case of conflict, the present document, including definitions, will control. Preferred methods and materials are described below, although methods and materials similar or equivalent to those described herein may be used in the practice or testing of the present disclosure. All publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety. The materials, methods, and examples disclosed herein are illustrative only and not limiting.
[0032] The numerical values in the specification and claims of the present application, particularly when they relate to polymers or polymer compositions, reflect the average values of compositions of individual polymers that can have different properties. Additionally, unless stated to the contrary, the numerical values should be understood to include the same numerical values when reduced to the same number of significant figures and numerical values that differ from the stated value by less than the experimental error of conventional measurement techniques of the type described in the present application for determining that value.
[0033] All ranges disclosed herein include the endpoints and can be combined independently (e.g., the range of "2 to 10" includes the endpoints 2 and 10 and all intermediate values). The endpoints and any values of the ranges disclosed herein are not limited to the exact ranges or values; they are sufficiently imprecise to include values approaching these ranges and / or values. As used herein, approximating language can apply to modify any quantitative representation that can vary without resulting in a change in the basic function associated therewith. Thus, in some instances, a value modified by one or more terms such as "about" is not limited to the specified exact value. In at least some instances, approximating language can correspond to the precision of the instrument used to measure the value. The modifier "about" should also be considered to disclose the range defined by the absolute values of the two endpoints. For example, the expression "about 2 to about 4" also discloses the range of "2 to 4". The term "about" can mean plus or minus 10% of the indicated number. For example, "about 10%" can represent the range of 9% to 11%, and "about 1" can mean 0.9 - 1.1. Other meanings of "about" can be apparent from the context, such as rounding, and thus, for example, "about 1" can also mean 0.5 to 1.4.
[0034] The present invention provides a sprayable hot melt adhesive that can be applied at 160 °C or below. Such a sprayable hot melt adhesive has high green strength and excellent adhesion strength. The sprayable hot melt adhesive can be applied in thin bond lines without the risk of bleeding and burning through of the heat-sensitive substrate.
[0035] One aspect of the present invention is a hot melt adhesive comprising about 20 - about 45 wt% of a polymer blend and 30 - about 60 wt% of a tackifier. The hot melt adhesive optionally comprises up to about 30 wt% of a wax or a polyolefin liquid plasticizer.
[0036] The polymer blend consists of:
[0037] (1) A first polypropylene - polyethylene (co)polymer having (i) a viscosity of 3000 cps to 8500 cps at 190 °C according to ASTM D3236, (ii) a DSC heat of fusion value of less than about 5 J / g measured at a heating rate of 10 °C / min according to ASTM D3418, and (iii) a DSC melting peak in the range of about 90 - 145 °C measured at a heating rate of 10 °C / min according to ASTM 3418; and
[0038] (2) A second polypropylene - polyethylene (co)polymer having (i) a melt index of about 15 - about 40 g / 10 min at 2.16 kg, 190 °C according to ASTM D1238, and (ii) a DSC heat of fusion value of less than about 15 J / g measured at a heating rate of 10 °C / min according to ASTM D3418;
[0039] In addition, the mass ratio of the first polypropylene-polyethylene (co)polymer to the second polypropylene-polyethylene (co)polymer is from about 3:1 to about 6.5:1. Surprisingly, the combination of the two polypropylene-polyethylene (co)polymers provides flexibility and adhesion in the adhesive even without the addition of rubber or amorphous polymers.
[0040] In another embodiment, the hot melt adhesive consists essentially of: about 20 - about 45 wt% of a polymer system, about 30 - about 60 wt% of a tackifier; about 10 - about 30 wt% of a wax or plasticizer; and about 0.1 - about 6 wt% of an additive selected from fillers, antioxidants, colorants, UV absorbers, UV inhibitors, pigments, compatible coatings for packaging purposes, etc.
[0041] The polymer system is a mixture of (1) a first polymer system and (2) a second polymer system, wherein the first polymer system has (i) a viscosity at 190 °C of from about 3,000 to about 8500 cps, preferably from about 5,000 to about 8,500, (ii) a DSC heat of fusion value of less than about 5 J / g measured at a heating rate of 10 °C / min according to ASTM D3418, (iii) a DSC melting peak at about 90 - 145 °C measured at a heating rate of 10 °C / min according to ASTM 3418, and (iv) propylene and ethylene (co)monomers; wherein the second polymer system has (i) a melt index of from about 15 - about 40 g / 10 min at 2.16 kg, 190 °C according to ASTM D1238, (ii) a DSC heat of fusion value of less than about 15 J / g measured at a heating rate of 10 °C / min according to ASTM D3418, and (iii) propylene and ethylene (co)monomers. The mass ratio of the first polymer system to the second polymer system is from about 3:1 to about 6.5:1.
[0042] It has been found that hot melt adhesives prepared with two specific polypropylene (co)polymers (in a specific ratio of from about 3:1 to about 6.5:1) provide flexibility for good initial strength and sufficient open time. This is achieved without additional rubber or amorphous polymers and without paraffin wax and naphthenic oil.
[0043] In one embodiment, the two polypropylene (co)polymers are amorphous in nature. The heat of fusion is directly related to the crystallinity of the polymer. For polypropylene (co)polymers of sprayable hot melt adhesives, a low level of crystallinity is desirable.
[0044] Suitable first polypropylene-polyethylene (co)polymers are amorphous poly-α-olefins (APAO) prepared by polymerization with Ziegler-Natta catalysts. Suitable amorphous poly-α-olefin polymers are random copolymers of propylene and ethylene monomers, including Aerafin 37 from Synthomer, DREX RT 2935 and DREX RT 2975 from REXtac LLC. Another suitable first polypropylene-polyethylene (co)polymer is an amorphous polypropylene copolymer prepared by polymerization with a metallocene catalyst. Suitable second polypropylene-polyethylene (co)polymers particularly include Vistamaxx 6502 from ExxonMobil Chemical. Polymer blends having specific viscosities / melt flow indices of the first and second polypropylene-polyethylene (co)polymers provide an appropriate balance of flexibility and cohesion for hot melt adhesives.
[0045] The tackifying resins available may include any compatible resin or mixtures thereof, such as aliphatic petroleum hydrocarbon resins; aromatic petroleum hydrocarbon resins and their hydrogenated derivatives; and alicyclic petroleum hydrocarbon resins and their hydrogenated derivatives. Examples of particularly suitable hydrogenated petroleum hydrocarbon tackifiers include Escorez 5400 and 5300 from Exxon Mobil Chemicals, Arkon P115 from Arakawa, Eastotac 100R, 100W, Regalite S1100 and R1100 from Eastman Chemical, LUHOREZ HD 1100 from Tianjin Luhua Chemical Co., Ltd, SUKOREZ SU-100 and SU-500 from Kolon Industries, HC-100 and HS-100 from Hanwha Solutions Corp, HM1000 from Henghe Materials & Science Technology Co., Ltd; HAITACK JH 6100 from Ningbo Jinhai Chenguang Chemical Corp, etc. Also included are cyclic or acyclic C5 resins and aromatic-modified acyclic or cyclic resins. Examples of commercially available C5 resins include Wingtack 98, Wingtackextra, Wingtack ET from Cray Valley USA LLC, Piccotac 9095 and 1095 from Eastman Chemical, Escorez 2203LC from Exxon Mobil Chemicals, Luhorez A1100, A2100 from Luhua Chemical Corp, Quintone R100 and C210 as well as S195 from Zeon Chemicals Co., Ltd. Also included are polyterpene resins; phenol-modified terpene resins and their hydrogenated derivatives, including, for example, resin products obtained by the condensation of bicyclic terpene and phenol in an acidic medium. Examples of commercially available modified terpene resins are Sylvares TR M1115 and TR126 from Kraton Chemical B.V. Sylvares 6100, NG98, TP 2040HM and Sylvares TP 300 from Kraton Chemical B.V., both of which are available from kraton chemical B.V.Examples of commercially available rosin and rosin derivatives useful for practicing the present invention include SYLVALITE RE 100L and SYLVARES RE 115 available from Kraton Chemical B.V.; hydrogenated rosins and rosin derivatives such as Foral 105 from Pinova Incorporated. Other useful tackifying resins include natural and modified rosins, including for example gum rosin, wood rosin, tall oil rosin, distilled rosin, hydrogenated rosin, dimerized rosin, resin acid esters, and polymerized rosin; glycerol and pentaerythritol esters of natural and modified rosins, including for example glycerol esters of pale wood rosin, glycerol esters of hydrogenated rosin, glycerol esters of polymerized rosin, pentaerythritol esters of hydrogenated rosin, and phenol-modified pentaerythritol esters of rosin; copolymers and terpolymers of natural terpenes, including for example styrene / terpene and alpha-methylstyrene / terpene.
[0046] Preferred tackifiers include C5 resins, petroleum distillates, hydrogenated hydrocarbons, C5 / C9 resins, C9 resins, polyterpenes, rosins, hydrogenated rosins, rosin esters, and mixtures thereof.
[0047] Also useful are C9 aromatic / aliphatic olefin-derived aromatic hydrocarbon resins, and are available under the trade name Norsolene from Sartomer and Cray Valley, and the series of TK aromatic hydrocarbon resins from Rutgers. Norsolene 1100 is a low molecular weight thermoplastic hydrocarbon polymer commercially available from Cray Valley.
[0048] Alpha-methylstyrenes such as Kristalex F 115, 1120, and 5140 available from Eastman Chemicals, and the Sylvares SA series from Arizona chemicals, can also be used as tackifiers for the present invention. Some formulations may require a mixture of two or more of the said tackifying resins.
[0049] Suitable waxes include paraffin wax, microcrystalline wax, polyethylene wax, polypropylene wax, by-product polyethylene wax, Fischer-Tropsch wax, oxidized Fischer-Tropsch wax, and functionalized waxes (such as hydroxystearamide wax and fatty amide wax). High-density low-molecular-weight polyethylene wax, by-product polyethylene wax, and Fischer-Tropsch wax are commonly referred to as synthetic high-melting-point waxes in the art. Useful waxes include polyethylene and polypropylene waxes, which can be obtained from the LICOCENE series, such as LICOCENE PE 4201, PE3101 from Clariant Corp, LICOWAX PE 520 and LOCTAS PE310 from Clariant Corp, Salsolwax H1 from SASOL Chemicals; Seration 1820 from SASOL Chemicals and the AC series from Honeywell International Inc such as AC-9, AC-8, AC-820A and L-C 101N from Lion Chemtech Co., Ltd.
[0050] The hot melt adhesives of the present invention are substantially free of any paraffin oil or naphthenic oil at room temperature. As used herein, "substantially free" or "free" is defined to include inevitable levels of impurities, but not additional impurities. Non-oil polyolefin liquid plasticizers are suitable as plasticizers in the hot melt adhesives. Suitable polyolefin liquid plasticizers include polypropylene, polybutene, polyisobutene, etc. Examples of commercially available non-oil polyolefin plasticizers are Indopol H100, H300, H900, H1500 from INEOS Oligomers; PB 950 from Daelim Industrial Co Ltd; TPC 1105, TPC 1160 from the TPC (Texas Petrochemicals) group; PIB 32, PIB 24 from Braskem S.A; Licocene PPA 330 from Clariant.
[0051] The sprayable low application temperature hot melt adhesives of the present invention may also desirably contain at least one stabilizer and / or at least one antioxidant. These compounds are added to protect the adhesive from degradation due to reaction with oxygen, which is induced by, for example, heat, light, or residual catalysts from raw materials such as tackifying resins.
[0052] The available stabilizers or antioxidants included in this article are high molecular weight hindered phenols and polyfunctional phenols, such as sulfur- and phosphorus-containing phenols. Hindered phenols are well-known to those skilled in the art and can be characterized as phenolic compounds that also contain bulky groups near their phenolic hydroxyl groups. In particular, tert-butyl groups are usually substituted at at least one ortho position relative to the phenolic hydroxyl group on the benzene ring. The presence of these bulky substituents near the hydroxyl group delays its stretching frequency and, accordingly, its reactivity; thus, this hindrance provides the phenolic compound with its stabilizing properties. Representative hindered phenols include; 1,3,5-trimethyl-2,4,6-tris-(3,5-di-tert-butyl-4-hydroxybenzyl)-benzene; pentaerythritol tetra-3(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate; n-octadecyl-3(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate; 4,4'-methylenebis(2,6-di-tert-butylphenol); 4,4'-thiobis(6-tert-butyl-o-cresol); 2,6-di-tert-butylphenol; 6-(4-hydroxyphenoxy)-2,4-bis(n-octylthio)-1,3,5-triazine; dioctadecyl thioethyl 3,5-di-tert-butyl-4-hydroxy-benzoate; and sorbitol hexakis[3-(3,5-di-tert-butyl-4-hydroxy-phenyl)-propionate].
[0053] These antioxidants are commercially available from BASF and include 565, 1010, 1076, and 1726, which are hindered phenols. These are the main antioxidants that act as free radical scavengers and can be used alone or in combination with other antioxidants such as phosphite antioxidants (such as 168, purchased from BASF, and EVERFOS 168, purchased from Everspring Chemical Company). Phosphite antioxidants are considered secondary antioxidants and are not usually used alone. These are mainly used as peroxide decomposers. Other available antioxidants are LTDP, purchased from Solvay, and 330, purchased from HM Royal, Evernox 10, purchased from Everspring Chemical Company, and BNX 1010, purchased from Mayzo. Many of these antioxidants can be used alone or in combination with other such antioxidants. These compounds are added to the melt in small amounts, usually less than about 10 wt%, and have no effect on other physical properties. Other compounds that can be added without affecting physical properties are pigments that add color, or fluorescent agents, to mention just a few. These additives are known to those skilled in the art.
[0054] Other additives that are commonly used in hot melt adhesives to meet different properties and specific application requirements can also be incorporated into the adhesive compositions of the present invention. Such additives include, for example, fillers, pigments, flow modifiers, dyes, ionic and non-ionic surfactants, compatible coatings to prevent the adhesives from sticking (adhering) together for packaging purposes, which can be incorporated into the adhesive formulation in small or larger amounts depending on the purpose.
[0055] The hot melt adhesive composition is prepared by melt blending the components at a temperature of about 150 °C to about 180 °C to form a homogeneous blend, typically for about two hours. Various blending methods are known in the art, and any method that produces a homogeneous blend can be used. The blend is then cooled and can be formed into pellets, chunks, micro-chunks, or blocks for storage or transportation as preformed adhesives. These preformed adhesives can then be reheated and melted for application to a substrate.
[0056] The resulting hot melt adhesive has (i) a tan(δ) value greater than about 30 at 140 °C and 10 rad / s and (ii) a melt viscosity of about 1,500 - about 11,000 cps at 150 °C as measured by ASTM 3236.
[0057] The hot melt adhesive composition is suitable for joining absorbent structured articles, particularly sanitary absorbent structured articles, including diapers, diaper pants, baby wipes, training pants, absorbent underpants, child care pants, swimwear, and other disposable garments; feminine care products, including sanitary napkins, wipes, menstrual pads, pantiliners, pant shields, tampons, and tampon applicators; adult care products, including wipes, pads, containers, incontinence products, and urine shields; clothing components; sports and recreational products; products for heat or cold therapy, medical gowns (i.e., protective and / or surgical gowns), surgical drapes, caps, gloves, masks, bandages, wound dressings, wipes, covers, containers, filters, disposable clothing, and mattresses, medical absorbent clothing, pads; construction and packaging supplies, industrial pads (including meat pads); products for cleaning and disinfection, wipes, covers, filters, towels, toilet paper, facial tissue, non-woven rolls, household comfort products including pillows, pads, cushions, masks, and body care products such as products for cleaning or treating the skin, laboratory coats, coveralls. The sprayable low application temperature adhesive can also be used for bottle labeling or other applications involving plastic bonding or removable pressure-sensitive adhesive applications.
[0058] Numerous modifications and variations of the present invention are possible without departing from the spirit and scope thereof, which will be apparent to those skilled in the art. The specific embodiments described herein are provided by way of example only and the present invention is limited only by the terms of the appended claims and the full scope of equivalents of those claims. Example
[0059] The present invention will be further described in the following examples, the purpose of including these examples is for illustration and not to limit the scope of the present invention in any way.
[0060] The heat of fusion (ΔH) and the melting temperature Tm of the polymer were measured by DSC (Differential Scanning Calorimeter, TA Instruments model Q1000 DSC) at a rate of 10 °C / min for heating and cooling cycles according to ASTM D3418.
[0061] The viscosities of the adhesive and the polymer were measured at 140 °C, 150 °C, 160 °C and 190 °C using a standard Brookfield viscometer, spindle 27 according to ASTM 3236.
[0062] Tan δ was obtained using a TA Dynamic Mechanical Analyzer (ARES-MLS) with a temperature ramp test from Orchestrators software version 7.2.0.4. This test used parallel steel plates (316 stainless steel, Part#708 - 00966 - 1, from TA instruments) with a diameter of 25 mm and separated by a gap of approximately 1 mm. The sample was loaded and then heated to 160 °C at the desired temperature, and once the equilibrium temperature of 160 °C was reached, the temperature ramp began. This procedure measured data every 10 seconds. The convection oven (ARES-LN2 type) was continuously purged with cold nitrogen. The cooling rate was 5 °C / min until 0 °C was reached. The convection oven was continuously purged with nitrogen. The frequency was maintained at 10 rad / s. The initial strain at the start of the test was 50% (at the outer edge of the plate). The automatic strain option in the software was used to maintain a torque that could be accurately measured throughout the test. This option was configured such that the maximum applied strain allowed by the software was 80%. If necessary, the automatic strain program adjusted the strain at each temperature increment. If the torque was below 19.62×10 -3 Nm, the strain was reduced by 5% of the current value. If the torque exceeded 117.72×10 -3 Nm, the torque was reduced by 25% of the current value. Between 19.62×10 -3 and 117.72×10 -3At a torque of Nm, no strain change occurred at this temperature increment. The shear storage modulus or elastic modulus (G') and the shear loss modulus (G") are calculated by software based on torque and strain data. tanδ is reported as G" / G' at 140 °C, i.e.,
[0063] tanδ = G" / G' (at 140 °C).
[0064] The polypropylene copolymers in the adhesive samples are summarized in Table 1.
[0065] Table 1. Polypropylene (co)polymer description
[0066]
[0067] *Exxon Mobile
[0068] **Synthomer
[0069] ***REXtac LLC
[0070] ****Evonik Industries
[0071] a Measured at 190 °C / 2.16 kg, ASTM D1238
[0072] b Measured at 190 °C, ASTM 3236
[0073] c Determined by DSC in accordance with ASTM D3418
[0074] The adhesive samples are shown in Table 2 as adhesive Examples D1, E1, J, L, and M. The adhesives are formulated with various polypropylene polymers and tackifiers, waxes, plasticizers, and antioxidants. HM-1000 is a hydrogenated hydrocarbon tackifier from Henghe Material & Science Technology Co., Ltd.; Licocene PE4201 is a polyethylene wax from Clariant; Licocene PPA 330 is a polyolefin liquid plasticizer from Clariant; Evernox 10 is an antioxidant from Everspring Chemical Company.
[0075] Table 2. Adhesive examples
[0076]
[0077] For each adhesive sample, the components were heated and mixed at 160 °C until homogeneous. The adhesive was then applied between two substrates to form an adhesive article. Two different adhesive articles were prepared. The first adhesive article (nonwoven - film) was formed by bonding a breathable polyester (poly) BR149 from a Clopay substrate and a 15 gsm nonwoven fabric from a PGI substrate with the adhesive sample. The second adhesive article (film - film) was formed by bonding an air - impermeable polyethylene film with a thickness of 0.65 mil to another air - impermeable polyethylene film using the adhesive sample. The adhesive was applied to the substrates at a line speed of 1000 feet per minute at 150 - 155 °C using a Signature Spray applicator head from Nordson Corp, where the coating weight was 2.5 gsm or 4 gsm. The initial adhesion strength results for the corresponding adhesive samples are shown in Table 3.
[0078] The initial adhesion strength of the sample was determined as:
[0079] Adhesion strength [g / in] = average peel force [g] / sample width [in].
[0080] The average adhesion strength was determined using at least 5 samples.
[0081] In a Sintech 1 / D Tensile Testing Machine (MTS, model 1500BZF-50, USA), the adhesion strength between the non-woven fabric and the film, as well as between the films, was measured for the samples in a mode I T-peel configuration using a tensile tester. The tensile machine was equipped with a high-precision 300 lb load cell. Using a precision cutter from Thwing-Albert Instruments Co., Philadelphia, PA, the test samples had a substantially straight shape. The sample size was chosen to achieve the desired strain with a force suitable for the instrument. The sample size was approximately 2 inches wide by approximately 6 inches long. The length of the sample was aligned with the machine direction (MD direction). The samples were equilibrated at 23 °C ± 2 °C for at least one hour and then tested at the same temperature. The holders and clamps were fitted with light jaws (a flat or bar line could be used), the size of which was suitable for the sample size being tested. The instrument was calibrated according to the manufacturer's instructions. The distance between the gripping force lines (gage length) was 1 inch, and this distance was measured with a steel ruler clamped beside the clamp. The force reading on the instrument was zeroed to account for the mass of the holders and clamps. The following procedure was used to prepare samples (2 inches wide by approximately 6 inches long) for T-peel testing. The laminated sample was separated approximately 1 inch at the top, and the polyester side and the non-woven fabric side were taped. The sample was mounted in the clamp in a T-peel configuration, where the film part of the T-peel sample was mounted in the bottom clamp and the non-woven part of the T-peel sample was mounted in the top clamp. The sample was mounted in the clamp with minimum slack. The crosshead was moved upward at a constant crosshead speed of 12 in / min, and the sample was peeled until the respective materials (non-woven fabric fibers and film) were completely separated. The force and elongation data obtained at a rate of 50 Hz during the peel were measured. The peel force (gram-force, gf) during the first 8-inch extension was reported as the mode I adhesion strength. The average initial adhesion strength was determined using at least 5 samples.
[0082] The preferred initial peel strength of the adhesive on a specific substrate is equal to or greater than 150 gf / inch. Generally, articles formed with an adhesive having a peel strength higher than 150 gf / inch provide substrate deformation and tearing, indicating failure at the substrate rather than failure of the adhesive bond.
[0083] Table 3. Adhesion properties
[0084]
[0085] * Substrate: breathable polyester, BR149 (from Clopay) bonded to 15 gsm non-woven fabric (from PGI)
[0086] **Substrate**: A non-breathable polyethylene film with a thickness of 0.65 mil is adhered to a second non-breathable polyethylene film with a thickness of 0.65 mil.
[0087] Adhesive samples J, L, and M provide an initial adhesion strength greater than 150 gf / inch. These adhesive samples are made from a first polypropylene-polyethylene (co)polymer having (i) a viscosity of 3,000 cps to 8,500 cps at 190 °C, (ii) a DSC heat of fusion value of less than about 5 J / g measured at a heating rate of 10 °C / min according to ASTM D3418, and (iii) a DSC melting peak at about 90 °C - 145 °C measured at a heating rate of 10 °C / min according to ASTM 3418.
[0088] Adhesive samples D1 and E1 were prepared with polymers other than the desired viscosity and / or melting temperature. They had very high viscosities, provided a poor adhesion pattern, or could not be sprayed at temperatures below 160 °C.
Claims
1. A hot melt adhesive, comprising: (a) about 20 wt% to about 45 wt% of a polymer mixture consisting of the following (1) and (2): (1) A first polypropylene-polyethylene (co)polymer having (i) a viscosity of 3000 cps to 8500 cps at 190 °C, (ii) a DSC melting heat value of less than about 5 J / g measured at a heating rate of 10 °C / min according to ASTM D3418, and (iii) a DSC melting peak at about 90 - 145 °C measured at a heating rate of 10 °C / min according to ASTM 3418; and (2) A second polypropylene-polyethylene (co)polymer having (i) a melt index of about 15 - about 40 g / 10 min at 2.16 kg, 190 °C according to ASTM D1238, and (ii) a DSC melting heat value of less than about 15 J / g measured at a heating rate of 10 °C / min according to ASTM D3418; wherein the mass ratio of the first polypropylene-polyethylene (co)polymer to the second polypropylene-polyethylene (co)polymer is about 3:1 to about 6.5:1; (b) about 30 wt% to about 60 wt% of a tackifier; and (c) Optionally present, up to about 30 wt% of a wax or a plasticizer; wherein the hot melt adhesive has (i) a tan(δ) value greater than about 30 at 140 °C, 10 rad / s and (ii) a melt viscosity of about 1,500 cps to about 11,000 cps at 150 °C measured according to ASTM 3236.
2. The hot melt adhesive according to claim 1, wherein the first polypropylene-polyethylene (co)polymer is prepared with a metallocene catalyst.
3. The hot melt adhesive according to claim 1, wherein the first polypropylene-polyethylene (co)polymer is prepared with a Ziegler-Natta catalyst.
4. The hot melt adhesive according to any one of claims 1 to 3, wherein the first polypropylene-polyethylene (co)polymer has a viscosity of 5000 cps to 8500 cps at 190 °C.
5. The hot melt adhesive according to any one of claims 1 to 4, wherein the second polypropylene-polyethylene (co)polymer has a melt index of about 15 - about 40 g / 10 min at 2.16 kg, 190 °C.
6. The hot melt adhesive according to any one of claims 1 - 5, wherein the tackifier is selected from C5 resins, petroleum distillates, hydrogenated hydrocarbons, C5 / C9 resins, C9 resins, polyterpenes, rosin, hydrogenated rosin, rosin esters, and mixtures thereof.
7. The hot melt adhesive according to any one of claims 1 - 6, wherein the wax is selected from polyethylene wax and polypropylene wax.
8. The hot melt adhesive according to any one of claims 1 to 7, wherein the plasticizer is a non-oil polyolefin liquid plasticizer selected from polybutene, polyisobutene, polypropylene, or mixtures thereof.
9. The hot melt adhesive according to any one of claims 1 to 8, wherein the hot melt adhesive is substantially free of oil.
10. The hot melt adhesive according to any one of claims 1 to 9 further comprises an additive selected from antioxidants, colorants, fillers, UV absorbers, UV inhibitors, pigments, compatible coatings for packaging purposes, and mixtures thereof.
11. A hot melt adhesive consisting essentially of: (a) from about 20 to about 45 wt% of a polymer matrix prepared from a mixture of (1) and (2): (1) a first polymer system having (i) a viscosity of 3000 - 8500 cps at 190 °C, (ii) a DSC heat of fusion value of less than about 5 J / g measured at a heating rate of 10 °C / min according to ASTM D3418, (iii) a DSC melting peak at about 90 - 145 °C measured at a heating rate of 10 °C / min according to ASTM 3418, and (iv) propylene and ethylene (copolymer) monomers; and (2) a second polymer system having (i) a melt index of about 15 - about 40 g / 10 min at 2.16 kg, 190 °C according to ASTM D 1238, (ii) a DSC heat of fusion value of less than about 15 J / g measured at a heating rate of 10 °C / min according to ASTM D3418, and (iii) propylene and ethylene (copolymer) monomers; wherein the mass ratio of the first polymer system to the second polymer system is from about 3:1 to about 6.5:1; (b) from about 30 to about 60 wt% of a tackifier; (c) from about 10 to about 30 wt% of a wax or plasticizer; and (d) from about 0.1 to about 6 wt% of an additive selected from antioxidants, colorants, fillers, UV absorbers, UV inhibitors, pigments, compatible coatings for packaging purposes, and mixtures thereof; wherein the hot melt adhesive has (i) a tan(δ) value greater than about 30 at 140 °C, 10 rad / s and (ii) a melt viscosity of about 1,500 - about 11,000 cps at 150 °C measured according to ASTM 3236.
12. An article comprising the adhesive according to any one of claims 1 to 11.
13. The article according to claim 12, wherein the adhesive is disposed between two substrates.
14. The article according to claim 13, wherein the substrates are selected from non-woven fabrics, polymer films, elastic films, and paper towels.
15. The article according to any one of claims 12 to 14, which is a diaper, training pants, absorbent underwear, swimsuit, sanitary napkin, tampon, disinfecting wipe, facial wipe, medical gown, meat pad, face mask, coverall, surgical drape, hat, glove, face shield, bandage, wound dressing, filter, mattress, pad, towel, toilet paper, facial tissue, or animal pad.
Citation Information
Patent Citations
Polyolefin-Based Hot Melt Adhesives With Improved Processing And Bonding Performance
US20160102230A1
Hot melt adhesive composition based on a blend of propylene copolymers prepared using single-site catalysts and methods for using same
US20170204306A1
High cohesive strength polyolefin construction adhesive
US20170290945A1
Hot melt adhesive compositions based on propylene-based polymers and methods for using same
US20190144719A1
Hot melt adhesive compositions including polyolefin and styrene block copolymers, and articles including the same
US20190382631A1